Factors associated with diet diversity among infants and young children in the Eastern and Southern Africa region - Yunhee Kang; Rebecca A. Heidkamp; Kudakwashe Mako‐Mushaninga; Aashima Garg; Joan N. Matji; Mara Nyawo; Hope C. Craig; Andrew L. Thorne‐Lyman (Maternal and Child Nutrition, 2023)
Abstract This study explores common factors associated with not meeting minimum dietary diversity (MDD) among 27,072 children aged 6–23 months in Eastern and Southern Africa using data from nine Demographic and Health Surveys from 2013 to 2016. MDD was defined as consumption of more than or equals to five of eight food groups including breast milk in the past 24 h. Equity gaps were calculated as the difference in MDD prevalence between the top and bottom wealth quintiles. Logistic regression was conducted to identify common factors for not meeting MDD at the household, maternal and child levels across two or more countries to inform regional policies to improve children's diets. Kenya had the highest MDD wealth equity gap (40.4 pts), and South Africa had the smallest (14.4 pts). Equity gaps for flesh foods or eggs (up to 39.8 pp) were larger than for grain or legumes (up to 20 pp). Common risk factors for not reaching MDD included younger child age (6–11 months) (n = 9 countries), no formal maternal occupation (n = 6), not receiving vitamin‐A supplementation (n = 3), younger maternal age (n = 3), lower maternal education (n = 3), no media (n = 3) or newspaper (n = 3) exposure, lower household wealth quintile (n = 3), use of nonefficient cooking fuel (n = 2), longer time to get to the water source (n = 2), not listening to the radio (n = 2) and higher birth order (n = 2). Priorities for improving MDD in the region include introducing diverse foods at a young age from 6 months with early nutrition counselling, promoting higher maternal education, increasing food purchasing power and ensuring the support of younger mothers.